Pendampingan Peningkatan Kapasitas Kader Posyandu Remaja Uswatun Hasanah Desa Cikunir Wilayah Kerja Puskesmas Singaparna - Santi Susanti; Fenty Agustini; Dina Nurfitriani Dewi; Tita Rosmiati (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Adolescent Reproductive Health Service is an activity and/or a series of activities aimed at adolescents in the context of maintaining reproductive health.Youth Integrated Service Post (Posyandu) is a form of Community-Based Health Efforts (UKBM) that is managed and organized from, by, for and with the community, including youth, in the implementation of health development, in order to empower the community and provide convenience in obtaining health services for adolescents to improve health status and adolescent healthy life skills. In Cikunir Village, Singaparna District, Tasikmalaya Regency, there is a youth Posyandu which has been running for 2 years. Based on information from youth cadres, there are 3 cadres who are not active. In this regard, it is necessary to recruit new youth cadres and enhance the capacity of youth cadres to increase their role in the implementation of youth posyandu. Objective: The purpose of this service was The purpose of this service was increase the capacity of youth posyandu cadres in managing posyandu.The target of the activity included youth posyandu cadres, prospective youth posyandu cadres from each hamlet and youth posyandu working groups in Cikunir village. Method: This public service was conducted by Observational method. Result: The results of the activity obtained increased knowledge of cadres about adolescent reproductive health counseling materials and increased youth skills in implementing the 5 table posyandu system and examination anthropometry. Conclusion: Cadre assistance is able to improve the knowledge and skills of cadres in the implementation of the Youth Integrated Service Post.